Combination of searches for Higgs boson decays into a photon and a massless dark photon using pp collisions at s $$ \sqrt{s} $$ = 13 TeV with the ATLAS detector - The ATLAS collaboration; G. Aad; E. Aakvaag; B. Abbott; S. Abdelhameed; K. Abeling; N. J. Abicht; S. H. Abidi; M. Aboelela; A. Aboulhorma; H. Abramowicz; H. Abreu; et al. (Journal of High Energy Physics)
Abstract A combination of searches for Higgs boson decays into a visible photon and a massless dark photon (H → γγ d) is presented using 139 fb −1 of proton-proton collision data at a centre-of-mass energy of s $$ \sqrt{s} $$ = 13 TeV recorded by the ATLAS detector at the Large Hadron Collider. The observed (expected) 95% confidence level upper limit on the Standard Model Higgs boson decay branching ratio is determined to be B $$ \mathcal{B} $$ (H → γγ d) < 1.3% (1.5)%. The search is also sensitive to higher-mass Higgs bosons decaying into the same final state. The observed (expected) 95% confidence level limit on the cross-section times branching ratio ranges from 16 fb (20 fb) for m H = 400 GeV to 1.0 fb (1.5 fb) for m H = 3 TeV. Results are also interpreted in the context of a minimal simplified model.